Acute buccal ulcer. - García-Montero, P.P.; Rojas-Mora, E.; González-Olivares, M.; Martínez-Morán, C.; Hernández-Núñez, A.; Cedeño, N.; González-Herranz, R.; Borbujo, J. (European Journal of Pediatric Dermatology, 2017)
The Authors describe an acute ulcer of the oral cavity arisen in a 14-year-old girl that regresses within 3 weeks. The serological tests showed IgM anti-Mycoplasma pneumoniae that disappeared after six weeks. After excluding other possible causes thanks to the history and laboratory examinations, the Authors suggest that the condition is an oral equivalent of ulcus vulvae acutum both for the clinical features and course of the lesions and for the role played by Mycoplasma pneumoniae in the vulvar localization.